2014
DOI: 10.15662/ijareeie.2014.0307003
|View full text |Cite
|
Sign up to set email alerts
|

Full Automation in Driverless Trains: A Microcontroller-Based Prototype

Abstract: Driverless trains are equipped with a control system, which is programmed to make them following a specific path. Stations on such a path, timings of the train and distances between stations are all predefined. Messages and warnings are automatically generated and announced to the passengers. This paper presents the development process of a prototype for a driverless train implemented using a PIC microcontroller. Simulation for the system's circuits is done with the aid of Proteus software. The hardware circui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The procedures adopted for the verification process in automated metro systems could be extended to other complex systems as well. Mohammed et al [64] developed a microcontroller-based prototype for ATs. The proposed AT prototype was able to perform a set of basic operations, including the following: (1) travel via a predefined path between a set of stations; (2) sensing the station arrival; (3) proper stopping at stations; and (4) display of synchronized messages regarding the train arrival at a given station.…”
Section: Design and Technologies For Autonomous Trainsmentioning
confidence: 99%
See 2 more Smart Citations
“…The procedures adopted for the verification process in automated metro systems could be extended to other complex systems as well. Mohammed et al [64] developed a microcontroller-based prototype for ATs. The proposed AT prototype was able to perform a set of basic operations, including the following: (1) travel via a predefined path between a set of stations; (2) sensing the station arrival; (3) proper stopping at stations; and (4) display of synchronized messages regarding the train arrival at a given station.…”
Section: Design and Technologies For Autonomous Trainsmentioning
confidence: 99%
“…The study indicated that the Combined Model-Based Analysis and Testing of Embedded Systems (MBAT) project conducted in the European Union would help improving the verification process. 36 Mohammed et al (2014) [64] Develop a microcontroller-based prototype for ATs.…”
Section: Design and Technologies For Autonomous Trains 30mentioning
confidence: 99%
See 1 more Smart Citation